Information clues and emotional intentions: A case study of the regional image of the cultural and creative community - Yulin Chen (Administrative Sciences, 2019)
In order to capture the value of cultural creativity, this study explored regional cultural creativities with different creative forms to understand how people interpret and interact with various regional cultural creative images. This was done by analyzing the abstract (performance) type of cultural creativity and the figurative (commodity) type of cultural creativity, in order to understand how existing regional cultural creativities operate information threads in social media, and how the different forms of content may lead to different levels of participation and feedback. The Cloud Gate Dance Theater can be taken as an example of an abstract cultural creation (performance type), and Green-in-hand as an example of a figurative cultural creativity (commodity type). In this study, all user page content for the period 1 January 2011, to 31 December 2018, and the number of user comments for each post were analyzed, for a total of 4784 posts. Computer science, data mining, big data, and social network analysis were combined to verify the findings of the analyses. Through an application programming interface (API), data and information in social media is extracted. Then data filtering, storage, and analysis is performed with meaningful information extracted for interpretation and for use in text mining to explore the relationship with the public based on content attributes. This study first verifies that the regional image is consistent with the social image location. Second, the information cues results found that information cues could be organized into region personality through any direct or indirect contact. Third, emotional clues can evoke emotions and self-expression, which is seen as an important clue to region emotions. In addition, this study also provides a conceptual framework for understanding how different forms of information, in regards to social management of existing regional cultural creativities, leads to varying levels of participation. Understanding the form of information is a key factor in the acceptance of information by the public. It is a reminder for cultural and creative institutions of the importance of text and images, and of figurative and abstract information planning in social content. In order to improve the competitiveness of the destination, using content interaction through social media to create and enhance a strong brand image is important.
Keywords: 350; social media content exploration; regional image; abstract and figurative clues; cultural and creative community